Politik Hukum Undang Undang Paten: Perbandingan Indonesia dan Jepang - Triganda Sayuti, Ageng; Windarto, Windarto; Pahlefi, Pahlefi; Naili Hidayah, Lili (Recital Review, 2024)
This article discusses the development of patent law formation in Japan as a country known to be superior in the field of technology, with a comparison of the development of patent law in Indonesia from the beginning of independence until after the reform era. By using normative methods. The results of the discussion of this paper show that firstly, intervention from various countries in various international agreements related to intellectual property was addressed by Japan with great consideration of economic aspects and in the end, Japan's patent regulations tended to follow America's common law legal tradition. Second, the formation of the Patent Law in Indonesia according to the period of its validity has experienced a shift, if initially the Patent Law was formed to encourage the improvement and development of domestic industry, in subsequent developments it was also influenced by the desire to follow international trade developments and politics by adapting the Law to TRIPs.